2017
DOI: 10.1093/geroni/igx017
|View full text |Cite
|
Sign up to set email alerts
|

A Question of Trust: Does Mistrust or Perceived Discrimination Account for Race Disparities in Advance Directive Completion?

Abstract: Background and ObjectivesAdvance directive completion is associated with end-of-life quality indicators such as dying at home and receiving hospice care. Black older adults are less likely to complete advance directives than their white counterparts. The underlying reasons for these race disparities are not well understood.Research Design and MethodsIn two related studies, data from the Health and Retirement Study were used to examine whether mistrust in health care providers and/or perceived discrimination ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…28 37 Hispanic and African Americans tend to trust their family to promote their end-of-life care and they more readily disclose to them their end-of-life wishes rather than complete formal documentation. 28,35,38,39 In countries other than the United States, there is also clear evidence of poor uptake of ACP by older people from diverse cultural and ethnic background, namely, in the United Kingdom by people of Black, Asian and Minority Ethnic (BAME) groups; 4 in Australia, there is low uptake by Aboriginal people 2 and in New Zealand, by Maori and Pacific populations. 1 There is scarce knowledge about perspectives of Indigenous American Indians’ and First Nation Peoples (Canada) regarding end-of-life treatments, which has resulted in health care providers functioning at less than optimum levels.…”
Section: Acp and Older People From Diverse Cultural And Ethnic Backgrmentioning
confidence: 99%
“…28 37 Hispanic and African Americans tend to trust their family to promote their end-of-life care and they more readily disclose to them their end-of-life wishes rather than complete formal documentation. 28,35,38,39 In countries other than the United States, there is also clear evidence of poor uptake of ACP by older people from diverse cultural and ethnic background, namely, in the United Kingdom by people of Black, Asian and Minority Ethnic (BAME) groups; 4 in Australia, there is low uptake by Aboriginal people 2 and in New Zealand, by Maori and Pacific populations. 1 There is scarce knowledge about perspectives of Indigenous American Indians’ and First Nation Peoples (Canada) regarding end-of-life treatments, which has resulted in health care providers functioning at less than optimum levels.…”
Section: Acp and Older People From Diverse Cultural And Ethnic Backgrmentioning
confidence: 99%
“…A systematic review of hospice use of Black people cited multiple factors contributing to relatively lower hospice utilization levels, including lack of hospice awareness, monetary concerns, mistrust of the health care system, a conflict in value with hospice care, and expected lack of racial/ethnic minority staff within hospice care (Washington, Bickel-Swenson, & Stephens, 2008). Alternately, Koss and Baker (2017) reported findings that question the common assertion that mistrust of the health system by Black older adults contributes to lower rates of advance care planning (a practice associated with receiving hospice care earlier and longer) (Bischoff, Sudore, Miao, Boscardin, & Smith, 2013; Teno, Gruneir, Schwartz, Nanda, & Wetle, 2007). Adams, Horn, and Bader (2007) emphasized the lack of access to health services prior to hospice admission for the U.S. Hispanic population as a significant reason for lower hospice use by that group.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this racial disparity, previous research 14,15 has assessed the role of medical mistrust and health care stereotype threat (ie, the threat that healthcare professionals will apply group stereotypes to patients 16 ). Although these variables have been shown to be negative predictors of ACP completion for Black patients, 14,17 they do not fully explain the racial disparity in ACP. Further, McAfee et al 12 found no significant association between perceived racial discrimination in healthcare settings and ACP completion.…”
mentioning
confidence: 99%